Immunogenicity of the drug "Live intranasal vaccine for the prevention of pertussis" (GamLPV) with a single use in healthy volunteers - A. Yu. Medkova; A. A. Lidzhiyeva; E. G. Semin; L. N. Sinyashina; R. A. Syundyukova; N. A. Snegireva; I. N. Chernyshova; M. V. Gavrilova; K. K. Bushkova; L. V. Kolobukhina; I. S. Kruzhkova; L. N. Merkulova; et al. (Журнал микробиологии, эпидемиологии и иммунобиологии, 2022)
Introduction. A significant increase in the incidence of pertussis in the world, including among adolescents and adults, the prevalence of mild forms of the disease and asymptomatic carrier of bacteria B. pertussis, and the resulting need for mass revaccination of different age groups determine the demand for new vaccines against B. pertussis. In N.F. Gamaleya Federal Research Center for Epidemiology and Microbiology, a live intranasal pertussis vaccine for the prevention of pertussis (GamLPV) has been developed. The GamLPV vaccine underwent preclinical studies that proved its safety and effectiveness in experiments on small laboratory animals and nonhuman monkeys. Safety of vaccine is shown in clinical studies on healthy volunteers.The aim of the study is to assess the immunogenicity of different doses of the drug GamLPV when first used in healthy volunteers.Materials and methods. The study was conducted as randomized placebo-controlled, blind trial with consistent volunteer inclusion and dose escalation. Study ID in clinicaltrials.gov database: NCT03137927 (A Phase I Clinical Study of a GamLPV, a Live Intranasal Bordetella Pertussis Vaccine). The following parameters of humoral and cellular immune responses were assessed in dynamics: levels of specific IgM, IgG and IgA antibodies in blood serum of volunteers and the number of cytokines interleukin-17, tumor necrosis factor-α, interferon-γ produced after specific induction in vitro of blood mononuclears of vaccinated volunteers. Dynamics of attenuated bacteria persistence in nasopharynx of vaccinated volunteers was evaluated.Results. Intranasal vaccination of volunteers with the drug Gam LPV resulted in the formation of a specific humoral (IgG and IgA) and cellular immune response. The dose-dependent nature of immunoglobulin and cytokine production was shown. Attenuated bacteria persisted for a long time in the nose/oropharynx of vaccinated volunteers.Discussion. Good tolerability of all tested doses of the drug justifies the choice for further investigation of a vaccine dose equal to 4 × 109 CFU. At the next stage, the safety and immunogenicity of two-time vaccination of volunteers will be studied.